Analysis of Regional Fixed Asset Management at the Regional Finance and Asset Agency (BKAD) of South Sulawesi Province - Nurhalisa Rahmat; Nur Afiah; Masdar Ryketeng (PT. Maju Malaqbi Makkarana, 2026)
This study aims to analyze the compliance of regional fixed asset management at the Regional Finance and Asset Agency of South Sulawesi Province with the provisions of Minister of Home Affairs Regulation No. 19 of 2016, with a focus on motorized two-wheeled vehicles. The research method used is qualitative descriptive, with data collection techniques involving interviews and documentation. The data used consists of primary data from the interviews as well as secondary data in the form of asset management documents and related reports. The results of the study indicate that asset management has generally been carried out in accordance with applicable regulations and covers all stages of management. However, there are still challenges regarding supervision, reporting, and asset user compliance, as well as relatively complex administrative procedures. Therefore, it is necessary to optimize controls and streamline procedures to improve accountability in asset management